Bilateral lateral ventricular subependymoma with extensive multiplicity presenting with hemorrhage. Issue 1 (February 2018) - Moinuddin, FM; Ikbar Khairunnisa, Novita; Hirano, Hirofumi; Hanada, Tomoko; Hiraki, Tsubasa; Kirishima, Mari; Kamimura, Kiyohisa; Arita, Kazunori
This 48-year-old-man who had undergone right thyroid lobectomy for undifferentiated thyroid carcinoma nine years earlier developed generalized seizures. His cerebrospinal fluid was xanthochromic with elevation of total protein. Computed tomography (CT) showed mixed-density bilateral ventricular masses. Magnetic resonance imaging (MRI) revealed multiple nodules in both lateral ventricles; they were heterogeneously enhanced by gadolinium. Diffuse hyperintensity in the right medial temporal lobe and bilateral subependymal area was noted on fluid-attenuated inversion recovery images. Susceptibility-weighted imaging showed low intensity in the masses and cerebellar sulci suggesting hemorrhage and hemosiderin deposition. The preoperative diagnosis was disseminated malignant tumor with recurring hemorrhage. Histological examination of biopsy specimens showed clusters of cells with small uniform nuclei embedded in a dense fibrillary matrix of glial cells and microcystic degeneration. Pseudo-rosettes indicating ependymoma were absent. Microhemorrhages and hemosiderin deposits were noted. Immunohistochemically, the background fibrillary matrix and neoplastic cells were positive for glial fibrillary acidic protein. Mutated isocitrate dehydrogenase-1 was negative. The MIB-1 index was 1.5%. The tumor was pathologically diagnosed as subependymoma containing microhemorrhages and hemosiderin deposits. The extensive multiplicity and hemorrhage encountered in this case have rarely been reported in patients with subependymoma.